2018
DOI: 10.1177/1940082918754777
|View full text |Cite
|
Sign up to set email alerts
|

Bird Community Assemblage and Distribution in a Tropical, Urban Ecosystem of Puerto Rico

Abstract: Urbanization has profound effects on the presence and distribution of wildlife species. Although numerous studies have been conducted to inform our understanding of the effects of urbanization on wildlife, studies of urban wildlife communities in the tropics are especially rare. Here, we investigated the bird community assemblage and distribution at an urban military installation, Fort Buchanan, located within the San Juan Metropolitan Area on the Caribbean island of Puerto Rico. Using fixed-radius point count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Among all habitat types, roads and urban areas showed the lowest species diversity and endemism in Southcentral Mindanao. Several studies have shown a similar pattern from ours where heavily urbanized areas show these patterns (Blair, 1996;Gamalo & Baril, 2018;Gatesire, Nsabimana, Nyiramana, Seburanga, & Mirville, 2014;Wolff, DeGregorio, Rodriguez-Cruz, Mulero-Oliveras, & Sperry, 2018). The presence of green spaces, that is, trees and available foraging sites has higher species richness (Suarez-Rubio et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…Among all habitat types, roads and urban areas showed the lowest species diversity and endemism in Southcentral Mindanao. Several studies have shown a similar pattern from ours where heavily urbanized areas show these patterns (Blair, 1996;Gamalo & Baril, 2018;Gatesire, Nsabimana, Nyiramana, Seburanga, & Mirville, 2014;Wolff, DeGregorio, Rodriguez-Cruz, Mulero-Oliveras, & Sperry, 2018). The presence of green spaces, that is, trees and available foraging sites has higher species richness (Suarez-Rubio et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…The importance of understanding the ecological effects of urbanisation cannot be under-emphasised, especially with its rapid conversion of previously wild lands around the world. The process associated with urbanisation has profound effects on the distribution of wildlife species and their habitats (Wolff et al 2018). Urban development is characterised by rapid population growth and profound land use transformation, leading to land conversion, which is a predominant process affecting ecological community structure and population dynamics of living organisms (Hostetler 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, conservation biologists have focused primarily on the protection of natural ecosystems and have placed little importance on urban areas or urban biodiversity [4]. To date, most studies on wildlife in cities have focused on birds [5,6]. However, few studies have focused on arthropods [7][8][9].…”
Section: Introductionmentioning
confidence: 99%